Program Penyuluhan Kewirausahaan Berbasis Digital Marketing Pada Desa Koto Sentajo, Sentajo Raya, Kabupaten Kuantan Singingi - Annisa Mardatillah; Rosmayani Rosmayani (PELANTAR PRESS, 2023)
This digital marketing-based entrepreneurship counseling activity was carried out at the PKK women's partner group in Koto Sentajo Village, Kuantan Singingi. The limited knowledge and skills oriented towards digital marketing-based entrepreneurship in the partner group of housewives of Sentajo Raya District, Kuantan Singingi is a problem that needs to be given a solution. The purpose of this PKM activity is to provide counseling and training to partner groups on digital marketing-based entrepreneurship in order to increase family income. The method provided is by conducting counseling or socialization programs and training related to entrepreneurship and digital marketing materials. The findings in the field after the service activities were that the PKK group of mothers in the village of koto sentajo, sentajo raya, Kuantan singing already had micro and small scale businesses with traditional food businesses such as puluik pucung, galamai, sago crackers and also sewing businesses. However, their marketing skills and limited capital make them less able to access a wider market. Utilization of digital media for online marketing can be utilized by using organic e-commerce media such as Facebook, WhatsApp and Instagram. The future target is to create a special website for marketing MSME products produced by local women.